Initial unsteady free convective flow past an infinite vertical plate with radiation and mass transfer effects - Khan, Ayub; Solanki, Ronak (Zielona Góra: Uniwersytet Zielonogórski)
An exact solution and analysis of an initial unsteady two dimensional free convection flow, heat and mass transfer in the presence of thermal radiation along an infinite fixed vertical plate when the plate temperature is instantaneously raised, is presented. The fluid considered is a gray, absorbing emitting radiation but a non-scattering medium. Three cases have been discussed, in particular, namely, (i) when, the plate temperature is instantaneously raised to a higher constant value, (ii) when, the plate temperature varies linearly with time and (iii) when, the plate temperature varies non-linearly with time.
Keywords: free convection flow; porous medium; heat transfer; mass transfer; MHD